Webinar Tips & Trik Jualan Online di Tokopedia (Jurnal Abdikarya: Jurnal Karya Pengabdian Dosen Dan Mahasiswa, 2021)
This service aims to socialize the use of online media, especially market places, as a means of marketing for MSMEs in Denpasar City with the hope of expanding the marketing area which will have an impact on increasing turnover, especially in the current pandemic. This activity uses a contextual approach method, namely providing information about government policies, especially the Denpasar City Industry and Trade Office, Tips and Tricks about entrepreneurship from National Polytechnic and Technical Lecturers to do online marketing at the market place, in this case in collaboration with Tokopedia. The results of the training show that the community service participants are very interested in participating in this kind of training because they really feel helped in utilizing online media as a means of marketing their products and making it easier for consumers to get service products produced by MSMEs.